The Impact of Covid-19 on National Security of Nepal - Giri, Susma (Unity Journal, 2021)
With the announcement of a nationwide lockdown from 24th March 2020 in Nepal, national security is no longer limited to the proper use of economic power, political authority, and diplomacy. Public and private offices have asked their employees to work from home in the online space considering the uncertainty about the end of the COVID-19 pandemic. The introduction of the ‘new normal’ to maintain physical distance and perform the task from cyber/online space has demanded the redefinition of the concept of national security, i.e., beyond the protection of nation and citizens from potential attacks and ensuring the guard of the state secrets. With the responsibility to undertake the regular duties including preparation for war, investigation of crimes, safeguard of national territories, and the establishment of peace and order, the security forces of Nepal are piled up with another challenging responsibility of preventing cybercrime and its by-product in this ongoing digital era. As the security forces of Nepal are occupied with the task to address the pandemic situation, it is likely that criminals and terrorists take advantage of it and cause rampant cybercrimes. Electronic Transaction Act, 2063B.S (2008A.D) is the major law that authenticates, regularizes, and controls the unauthorized use of electronic records in Nepal. This article focuses on the discussion if more than a decade older Act is sufficient to address the new cyber issues mushrooming in speedily running cyberspace. This article aims to explore various impacts of the COVID-19 pandemic on different aspects of the national security of Nepal with special emphasis on cyber security. The study is conducted based on data obtained from different sources. Published articles, news, documentaries, and comparative study related to the impact of the COVID-19 pandemic on national security are searched and reviewed for this study.